Analisis Program Darussalam Memberi Solusi (DASI) di Radio Darussalam - Abdi Fauji Hadiono; Sugiyono Sugiyono; Ahmad Aid Alfaizin (IAI Darussalam, 2020)
Every program presented by the mass media should meet the needs of each user. Likewise, programs on the radio are required to have good values. This research was conducted to analyze 1) the pre-production process of the Darussalam Giving Solutions (DASI) broadcast program, 2) the production process of the Darussalam Giving Solutions (DASI) broadcast program. The method used is a qualitative approach. Data collection techniques using interviews, observation, documentation. Data analysis used an interactive model from Milles and Huberman. The results showed 1) the pre-production stage, Radio Darussalam was very well planned, namely holding a meeting in determining material themes based on trends that occurred in the community and determining competent presenters to discuss the material described, 2) the production stage, namely the application from the planning stage of the Darussalam Giving Solutions program, using a talk show format to send questions via Whatsapp messages, SMS, telephone and via comments on the Facebook live stream. This program is also a place to provide kindness and insight for loyal listeners.